ANALISIS PERILAKU PENCEGAHAN PENULARAN HIV/AIDS PADA IBU HAMIL DI PUSKESMAS KALIKAJAR 1 WONOSOBO - ., Romdiyah; Nugraheni, Nazilla (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
HIV infection in pregnant women can threaten the life of the mother and the mother can transmit the virus to her baby. Prevention of HIV for pregnant women should be done in the first trimester or second trimester so as to improve the health of HIV positive mothers. The purpose of this study was to analyze the factors that influence the prevention behavior of HIV / AIDS in pregnant women in Puskesmas Kalikajar 1 Wonosobo. Non experimental (observational) research type with cross sectional design. The population in the study was 60 people. The sampling technique used in this study used total sampling or saturated sampling with the number of 60 pregnant women. The analysis used is univariate, biavariat and multivariate analysis. The results showed that variables related to HIV / AIDS prevention behavior were knowledge of prevention of HIV / AIDS transmission, attitudes toward prevention of HIV / AIDS transmission, family support, and support of health personnel. The result of multivariate analysis shows that the support of health workers (p value = 0.002) is the variable that has the most significant effect on the prevention behavior of HIV / AIDS with OR of 14,562. Suggestion given to Expected further increase intensity of socialization about the importance of HIV / AIDS screening in pregnant woman. Keywords: HIV / AIDS, pregnant women, preventive behavior